Identification of some microbial genera associated to the maize crop (zea mays l) in different cuban soils (2003)
It has been demonstrated that applying bio-products based on native rhizosphere micro-organisms in agriculture increases crop productivity. Working with native strains also improves their biological feasibility. Some microbial genera associated with the improved corn variety Francisco were isolated from Nitisol Rhodic, Cambisol Eutric-Humic and Cambisol Eutric soil from different Cuban regions using three isolation methods: the convencional method, the spermosphere model and the microcosm model. The isolated micro-organisms were classified by using classic techniques. The results showed that Pseudomonas, Azospirillum, Azotobacter, Bacillus and Streptomyces were part of the corn rhizosphere microbial community structure, constituting Pseudomonas, this being the most promi-nent populación. All three evaluated isolation methods were suitable for obtaining typical microbial populations; however, the Spermosphere and Microcosm Models were seen to be superior for this purpose as they allow micro-organisms able to live at the expense of crop's exuded roots to become isolated in plant-bacteria interaction. Key words: rhizosphere, corn, spermosphere model, microcosm model, pseudomona